Juvenile Psammomatoid Ossifying Fibroma with Visual Disturbance: A Case Report with Imaging Features. Issue 1 (23rd June 2011) - Nakajima, Reiko; Saito, Naoko; Uchino, Akira; Kuji, Ichiei; Suzuki, Tomonari; Nishikawa, Ryo; Yamaguchi, Hiroshi; Kimura, Fumiko
ABSTRACT Juvenile psammomatoid ossifying fibroma (JPOF) of the sphenoid sinus is a rare subtype of ossifying fibroma of the sinonasal cavity and facial bone in young adults. Computed tomographic (CT) and magnetic resonance (MR) imaging features of JPOF have been reported, but to our knowledge, positron emission tomography (PET) findings have not been described. We present a 19‐year‐old woman with right visual disturbance whom we diagnosed with JPOF and describe imaging findings in her case. CT revealed a well‐circumscribed fibro‐osseous mass surrounding the right optic canal, with expansile, mixed soft tissue and thick bone density. MR imaging showed low signal intensity in the mass on both T1‐ and T2‐weighted images. [18F]fluorodeoxyglucose ([18F]FDG) and [11C]methyl‐L‐methionine ([11C]Met) PET/CT showed abnormal uptake in the lesion, with standardized uptake values (SUV) of 6.2 ([18F]FDG) and 4.6 ([11C]Met). Familiarity with the imaging features of this rare disease aids its differentiation from other more familiar lesions to permit appropriately aggressive therapy and improve prognosis.